Contrasting engineering effects of leaf-rolling caterpillars on a tropical mite community - Lima, Vivian O. [UNESP]; Demite, Peterson R.; Vieira, Camila; Feres, Reinaldo J. F. [UNESP]; Romero, Gustavo Q. (Wiley, 2013)
Ecosystem engineers are organisms that change the physical structure of environments and provide habitats for other organisms. Lepidopteran caterpillars may act as ecosystem engineers by rolling leaves as shelters to complete metamorphosis. After being abandoned, these structures may provide shelter for other organisms. In this study, the influence of leaf-rolling caterpillars on tropical mite communities was reported. Expanded leaves and leaves rolled by larvae and also developed field experiments using leaves rolled manually with different shapes and sizes (i.e. different architectures) in different seasons were surveyed (dry and rainy). While the abundance and diversity of predatory mites were higher in rolled leaves, the abundance of phytophages decreased in these leaves. Species composition differed between rolled and expanded leaves. The structure of shelters affected the distribution of predatory mites, with higher abundances found on funnel-shaped leaves. Predatory mites only benefited from the rolled leaves in the dry season. This is the first study showing (i) the contrasting effects of ecosystem engineers on microarthropod communities, favouring some feeding guilds and inhibiting others; (ii) that the shape of rolled leaves has variable effects on mite communities; and (iii) that facilitation was temporally dependent, i.e. occurred only in the dry season. © 2013 The Royal Entomological Society.
Keywords: Croton floribundus; Ecosystem engineering; Facilitation; Indirect effects; Inhibition; Leaf-rolling caterpillars; Mite-plant interactions; abundance; caterpillar; community structure; dry density; experimental study; field method; leaf; metamorphosis; mite; seasonal variation